Panelist acceptance level on milk chocolate bar with cinnamon (Cinnamomum burmannii) powder addition - INTAN NISA RASULUNTARI; DIMAS RAHADIAN AJI MUHAMMAD; DANAR PRASEPTIANGGA (Smujo International, 2016)
Abstract. Rasuluntari IN, Muhammad DRA, Praseptiangga D. 2016. Panelist acceptance level on milk chocolate bar with cinnamon (Cinnamomum burmannii) powder addition. Nusantara Bioscience 8: 297-300. Among confectionery products, milk chocolate bar is the most popular product. The development of Indonesian cocoa agroindustry and chocolate signature with special characteristics are required since Indonesia is the third largest cocoa producing country in the world. The effects of cinnamon powder addition in milk chocolate and its impact on the consumer acceptance of milk chocolate were evaluated in this study. Cinnamon-enriched milk chocolates were formulated by completely randomized design (CRD) with one factor which was concentration of cinnamon powder (5%; 10%; and 15%). Sensory evaluation (color, aroma, taste, appearance, overall) were determined by hedonic test with scoring method. The results showed that the level of panelist acceptance decreased with increasing concentrations of cinnamon powder added. Milk chocolate bar with the addition of 5% of cinnamon powder had the highest level of acceptance and preferences for some of the sensory attributes evaluated.